2011
DOI: 10.1093/eurjhf/hfr128
|View full text |Cite
|
Sign up to set email alerts
|

Does the physical examination still have a role in patients with suspected heart failure?

Abstract: AimsThe prognostic value of signs of congestion in patients suspected of having chronic heart failure (CHF) is unknown. Our objectives were to define their prevalence and specificity in diagnosing CHF and to determine their prognostic value in patients in a community heart failure clinic. Methods and resultsAnalysis of referrals to a community clinic for patients with CHF symptoms. Systolic CHF (S-HF) was defined as left ventricular ejection fraction (LVEF) ≤45%, heart failure with normal ejection fraction (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 32 publications
1
27
0
5
Order By: Relevance
“…Nevertheless, a former study showed that diuretic therapy could safely be withdrawn for a large proportion of very old geriatric patients, regardless of the initial indications, thus protecting them from the above‐mentioned furosemide complications and adverse effects. In addition, congestive signs, especially lower‐limb oedema, are particularly frequent among older patients, but are not specific to HF . It is not always easy to affirm their cardiac origin in ambulatory medicine, because of the limited access to confirmatory diagnostic tools (eg, echocardiography).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a former study showed that diuretic therapy could safely be withdrawn for a large proportion of very old geriatric patients, regardless of the initial indications, thus protecting them from the above‐mentioned furosemide complications and adverse effects. In addition, congestive signs, especially lower‐limb oedema, are particularly frequent among older patients, but are not specific to HF . It is not always easy to affirm their cardiac origin in ambulatory medicine, because of the limited access to confirmatory diagnostic tools (eg, echocardiography).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs of fluid overload are associated with an adverse outcome in patients with heart failure (HF), both in those with reduced and those with normal left ventricular (LV) systolic function, with or without common rhythm disturbances, such as atrial fibrillation (AF)1 2…”
Section: Introductionmentioning
confidence: 99%
“…However, crackles in IPF are heard throughout the entire inspiratory time [29,30]. Adventitious sounds associated with heart failure and pneumonia are higher in frequency and quite distinct from fine crackles of IPF [15,31], and rales are present in only one in four patients with left heart congestion due to systolic heart failure [32].…”
mentioning
confidence: 99%